2009
DOI: 10.4314/ijbcs.v2i4.39765
|View full text |Cite
|
Sign up to set email alerts
|

Etude de la variation de quelques caractères morphologiques d\'un échantillon de <i>Sclerocarya birrea</i> au Burkina Faso

Abstract: Le prunier d'Afrique, Sclerocarya birrea (A. Rich.) Hochst., est une Anacardiaceae principalement des savanes sahélo-soudaniennes. La sous espèce birrea, très répandue en Afrique Occidentale demeure sous utilisée. La description morphologique de 103 pieds de S. birrea subsp birrea le long d'un transect Nord-Sud (gradient climatique) au Burkina Faso a été faite en utilisant 15 caractères quantitatifs du fruit et du port des arbres. Cette étude a mis en évidence l'existence d'une variabilité et de différences tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 5 publications
5
7
0
2
Order By: Relevance
“…At least, two kernels are extracted per fruit (Bationo-Kando et al, 2008). The higher productivity of this fruit species and its presence in the form of plant communities, account for the commercial and industrial exploitation of its fruit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least, two kernels are extracted per fruit (Bationo-Kando et al, 2008). The higher productivity of this fruit species and its presence in the form of plant communities, account for the commercial and industrial exploitation of its fruit.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies to date, have focused on genetic diversity (Bationo-Kando et al, 2012), morphology (Bationo-Kando et al, 2008), anatomy (Sérémé, 1996;Diallo et al, 2006), or on the physicochemical composition of S. birrea the fruit (Bationo-Kando et al, 2009). On the other hand, data on the production and exploitation of the plant, by rural and urban populations, are still basic or non-existent.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of variance ( (Table 3) varies slightly from 11.22 to 12.90 mm with a coefficient of variation between 16.70% and 20.15%.…”
Section: Leaf Length (Lgf) and Leaf Width (Largf)mentioning
confidence: 99%
“…[4] in Burkina Faso indicated that the same Morphometric parameters underlined by [6] characterize with high variability baobab. As afr as Sclerocarya birrea is concerned, discriminative parameters are the diameter of fruits, the number of seeds, the seeds weight, the bole height and the number of primary branches [8]. [35] underlined that the individuals of Parkia biglobosa from Kalalé locality in Benin showed high means values of pods weight, the number of seeds per pods and the number of pods per infuriating and can be used for varieties selection.…”
Section: Morphometric Characteristics Of P Africanamentioning
confidence: 99%
“…Many studies had already concerned the variability of species showing great interest to the local populations. Among studies concerning morphological variability of species, one can underline those of [4] on Adansonia digitata in Mali, [5] on Argania spinosa in the South-West Morocco, [6] on Adansonia digitata in Benin, [7] and [8] on Sclerocarya birrea in Benin and in Burkina Faso, and [9] on Milicia excelsa. Some studies related to morphologic variability of Prosopis species were carried out by selected authors such as [10] on Prosopis juliflora and Prosopis pallida, of [11] and of [12].…”
Section: Introductionmentioning
confidence: 99%